2023
DOI: 10.3390/polym15112541
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Butterfly Pea Flower (Clitoria ternatea L.): Extraction and Application as a Food Freshness pH-Indicator for Polymer-Based Intelligent Packaging

Abstract: The butterfly pea flower (Clitoria ternatea L.) (BPF) has a high anthocyanin content, which can be incorporated into polymer-based films to produce intelligent packaging for real-time food freshness indicators. The objective of this work was to systematically review the polymer characteristics used as BPF extract carriers and their application on various food products as intelligent packaging systems. This systematic review was developed based on scientific reports accessible on the databases provided by PSAS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The groups attached to the chromophore affect the molecule's absorption spectrum, shifting it toward longer wavelengths ( Campbell, Pearson, & Marble, 2019 ). These findings align with previous research that indicated the stability of anthocyanin depends on factors such as pH, with low pH levels enhancing stability, as well as the influence of light ( Hasanah et al, 2023 ). This phenomenon, known as Bathochromic or a red shift, refers to the alteration in the absorption or emission wavelengths of a substance, often resulting in a change in color.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The groups attached to the chromophore affect the molecule's absorption spectrum, shifting it toward longer wavelengths ( Campbell, Pearson, & Marble, 2019 ). These findings align with previous research that indicated the stability of anthocyanin depends on factors such as pH, with low pH levels enhancing stability, as well as the influence of light ( Hasanah et al, 2023 ). This phenomenon, known as Bathochromic or a red shift, refers to the alteration in the absorption or emission wavelengths of a substance, often resulting in a change in color.…”
Section: Resultssupporting
confidence: 92%
“…At neutral pH, resonance-stabilized quinonoid anions, representing the purple color of anthocyanins, form through further deprotonation of the quinonoidal species ( Coutinho, Freitas, & Maçanita, 2015 ). The alteration in the color of BPE extracts across various pH levels is attributed to changes in the structure of anthocyanin pigments, which depend on the number of hydroxyl groups within the molecule ( Hasanah, Mohamad Azman, Rozzamri, Zainal Abedin, & Ismail-Fitry, 2023 ). Anthocyanins are classified as phenolic compounds, characterized by a chromophore with a benzene ring.…”
Section: Resultsmentioning
confidence: 99%
“…In the combined flour sample, antioxidant activity increased with adding butterfly pea flower powder due to its bioactive content. The anthocyanin content in butterfly pea flowers has been widely used over the years as a potential antioxidant [34]. This is consistent with the increase in total polyphenol value and antioxidant activity.…”
Section: Total Polyphenols and Antioxidant Activity Mixed Floursupporting
confidence: 70%
“…The ternatins found in BPF are more stable, so fading becomes less of an issue. 35 Additionally, BPF is safer than other common educational synthetic indicators such as phenolphthalein, which is a GHS-classified health hazard. For example, the food-safe and indicator properties of BPF have facilitated its use as a freshness monitor of seafood.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, this polyphenolic structure is susceptible to oxidation, which can cause the colors to fade. The ternatins found in BPF are more stable, so fading becomes less of an issue . Additionally, BPF is safer than other common educational synthetic indicators such as phenolphthalein, which is a GHS-classified health hazard.…”
Section: Introductionmentioning
confidence: 99%